Fighting Egoism in Freedom of Religion and Belief (Case Study: Communities Around the Keraton Solo Hadiningrat) - Etikasari Agus, Ratna (Institut Agama Islam Negeri Ponorogo, 2024)
Freedom of religion and worship in accordance with religion and belief has been regulated in the 1945 Constitution of the Republic of Indonesia. Harmonization in respecting and respecting freedom of religion and worship must put aside egoism. The purpose of this study is to analyze examples of harmonization in freedom of religion and worship in a society that still maintains its beliefs but that still adheres the religion that is state-recognized religion. This study uses a qualitative method. Data collection was carried out through literature studies, participant observation, and interviews. The methods used to analyze the data are data reduction, data presentation, and drawing conclusions. The results of this study are: 1) Kejawen Islamic Society and Islamic Santri can tolerate and respect each other; 2) Kejawen Islamic Society and Islamic Santri have an understanding that worship is a personal or private matter between adherents of religions and God Almighty; and 3) A sense of egoism in society is put aside because of the understanding that the area is an area that historically and culturally has strong ties. The implication of this research is that it is an example for every society, which until now has still questioning the freedom of religion and belief of other people.